(untitled) (Economics and region, 2023)
The article is devoted to the analysis of the concepts of "force majeure" and "force majeure" as circumstances of exemption from responsibility for non-fulfillment or improper fulfillment by the counterparty of its obligation under the contract. This is necessary to determine the possibility and necessity of distinguishing such concepts and their scientific research in the future. The article defines which circumstances can be recognized as force majeure , and also examines and examines the powers of the Chamber of Commerce and Industry of Ukraine as an entity authorized to confirm the existence of force majeure and issue the corresponding certificate. The position is argued that when issuing a certificate of force majeure, it is necessary to take into account how exactly this or that circumstance affects the proper fulfillment of the terms of the contract and whether there is a cause-and-effect relationship between the event and the inability of one of the parties to properly fulfill their obligations, since the mere presence of such events is not enough. The main types of force majeure circumstances and possible instruments of influence on contractual relations are considered, and a brief description of them is given. The issue of the possibility of exemption from liability for non-fulfillment of obligations has been investigated. Considerable attention is paid to the question of how to prove to the counterparty the real presence of force majeure circumstances, due to which they are deprived of the opportunity to fulfill the obligations assumed, that is, to substantiate that it was precisely because of armed aggression or because of military actions that they did not have any opportunity to fulfill and fulfill contractual obligations. It was concluded that every business entity should be clearly aware that force majeure does not allow avoiding the fulfillment of obligations, including financial ones. However, circumstances of force majeure allow the postponement of obligations or release from responsibility of the economic entity for their non-fulfillment during the existence of such circumstances (fines, damages). In terms of contractual relations, business entities were recommended to analyze their current contracts in detail, determine their future fate, apply the necessary legal norms and necessarily discuss all these issues with the counterparty.